Konstruksi Makna Hijab di Era Modern: Kajian Tafsir Kontekstual Abdullah Saeed - Mohamad Kharis Alwi; Mokhammad yahya; Ahmad Kholil (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This research is motivated by the emergence of diverse understandings and practices of hijab among contemporary Muslim communities, particularly regarding the meanings of hijab, jilbab, and khimār, which are often understood as obligations tied to specific forms of dress. The study aims to analyze the meanings of the Qur’anic verses on hijab (QS. al-Ahzab 33:53, QS. al-Ahzab 33:59, and QS. an-Nur 24:31) using Abdullah Saeed’s contextual interpretation approach in order to formulate an understanding of hijab that is relevant and applicable in the present context. The research employs a qualitative method based on library research. The findings indicate that the Qur’anic injunctions concerning hijab are instructional in nature and closely bound to the socio-historical context of the seventh century, rather than prescribing a fixed or uniform model of clothing. QS. al-Ahzab 33:53 emphasizes the ethics of maintaining privacy, QS. al-Ahzab 33:59 highlights the social function of the jilbab as a means of protection and identity, while QS. an-Nur 24:31 focuses on modesty and the safeguarding of modesty (ʿawrah). Universally, hijab embodies values of modesty, dignity, protection, and identity, while its physical forms may adapt to cultural contexts and historical developments, provided that the fundamental principles of Islamic law particularly propriety and the protection of women’s dignity are upheld.